Electrochemical sensing of urinary progesterone with molecularly imprinted poly(aniline-co-metanilic acid)s. Issue 21 (5th May 2016) - Lee, Mei-Hwa; O'Hare, Danny; Guo, Han-Zhang; Yang, Chien-Hsin; Lin, Hung-Yin
Abstract : The sensing of urinary progesterone with molecularly imprinted poly(aniline- co -metanilic acid) coated electrodes. Abstract : In this work, progesterone is imprinted into poly(aniline- co -metanilic acid) on the working electrode of an electrochemical sensing chip. This sensing chip was used directly to optimize the composition of the imprinting polymer. Poly(aniline- co -metanilic acid) deposited from a 1 : 3 molar ratio of aniline (ANI) :  m -aminobenzenesulfonic acid (MSAN) had an imprinting effectiveness which led to a four-fold greater electrochemical response than pure polyaniline. The electrochemical sensing of progesterone had a limit of detection (LOD) less than 1.0 pg mL −1, and the direct electrochemical response was very weak even at high interference concentrations. Results from potential interferents (urea, testosterone, creatinine and 17-β estradiol) are reported. The progesterone levels that were measured in a random urine analysis were compared with those obtained using a commercial ARCHITECT system, and the accuracy of the progesterone concentration was 89.0 ± 5.3% at a concentration of 0.64–5.27 ng mL −1 .